Теоретичний підхід до якісті дистанційного навчання - Weis, Lidija (Dr. Viktor Koval, 2021)
Introduction. Over the past decade, as technology coupled with the increasingly frequent use of the internet have become the forefront of business and academia, e-learning has emerged on the global higher education stage as a leading means of gaining an education in Higher Education. Because internet-based learning is currently such a relevant topic, inter alia due to the occurrence of the pandemic, there is a dire need for the creation of a common language to proceed in a collectively positive direction regarding the development of a culture of excellence within e-learning. This paper provides a springboard to discuss the underlying issues and challenges related to quality of internet-based learning, including the need for right measuring, and understanding dimensions of e-learning quality. Aim and tasks. The quality of education needs to be addressed (measured and managed) comprehensively, which means that, in addition to pedagogical aspects, it is also necessary to address the market quality. Therefore, a distinction must be made between quality that meets specifications (standard quality) and quality that meets expectations. Therefore, the main aim of the article is to review the different definitions of quality in e-learning and the dimensions that must be included in measuring the quality of e-learning. Results. Based on an extensive review of the literature on quality in e-learning, we conclude that the quality of e-learning cannot be viewed only from the student's perspective, but from the point of view of all participants in the e-learning process. In addition to pedagogical aspects, organizational, economic, and legal aspects must also be considered. What dimensions are key to measuring quality in e-learning thus remains a question to be answered. Conclusions. The quality of e-learning depends on many factors. Despite many discussions about quality and the search for appropriate dimensions of quality in e-learning, there is still no single evaluative standard. Because of this, effective qualitative metrics for e-learning are urgently required.